Enzootic mosquito vector species at equine encephalitis transmission foci in the República de Panamá - Torres, Rolando; Samudio, Rafael; Carrera, Jean-Paul; Young, Josue; Márquez, Ricardo; Hurtado, Lisbeth; Weaver, Scott; Chaves, Luis Fernando; Tesh, Robert; Cáceres, Lorenzo (PLOS ONE, 2017)
The identification of mosquito vector species present at arboviral enzootic transmission foci is important to understand transmission eco-epidemiology and to propose and implement prevention and control strategies that reduce vector-borne equine encephalitis transmission. The goal of this study was to identify mosquito species potentially involved in the transmission of enzootic equine encephalitis, in relation to their abundance and diversity at three endemic regions in the República de Panamá. We sampled adult mosquitoes during the dry and rainy season of Panamá. We employed CDC light traps with octanol, EV traps with CO2 and Trinidad 17 traps baited with live hamsters. Traps were deployed in the peridomicile and extradomicile of houses from 18:00 to 6:00 h. We estimated the abundance and diversity of sampled species. We collected a total of 4868 mosquitoes, belonging to 45 species and 11 genera, over 216 sampling nights. Culex (Melanoconion) pedroi, a major Venezuelan equine encephalitis vector was relatively rare (< 2.0% of all sampled mosquitoes). We also found Cx. (Mel) adamesi, Cx. (Mel) crybda, Cx. (Mel) ocossa, Cx. (Mel) spissipes, Cx. (Mel) taeniopus, Cx. (Mel) vomerifer, Aedes scapularis, Ae. angustivittatus, Coquillettidia venezuelensis, Cx. nigripalpus, Cx. declarator, Mansonia titillans, M. pseudotitillans and Psorophora ferox all species known to be vectorially competent for the transmission of arboviruses. Abundance and diversity of mosquitoes in the sampled locations was high, when compared with similar surveys in temperate areas. Information from previous reports about vectorial competence / capacity of the sampled mosquito species suggest that sampled locations have all the elements to support enzootic outbreaks of Venezuelan and Eastern equine encephalitides.